2011
DOI: 10.1111/j.1469-8749.2011.04014.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress and children with cerebral palsy: a European cross‐sectional survey

Abstract: AIM The aim of this study was to describe stress in the parents of children with cerebral palsy and investigate associations with very high stress.METHOD A cross-sectional survey was conducted of parents of 818 children aged 8 to 12 years from nine regions in Europe. Families were eligible to participate if they were living in one of the specified geographic areas. Parental stress was captured using the Parenting Stress Index Short Form, which has 36 items and takes 10 minutes to complete. Parents rate items o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
103
1
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 32 publications
7
103
1
13
Order By: Relevance
“…Mothers who have children with ASD are likely to experience mental health problems beyond high stress levels (Parkes, Caravale, Marcelli, Franco, & Colver, 2011; Raina et al, 2005). Compared to mother caregivers of children with other disabilities, it has been reported that caregivers of children with ASD have higher levels of depression and anxiety but lower levels of psychological wellbeing (Benson & Karlof, 2009; Ekas, Whitman, & Shivers, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Mothers who have children with ASD are likely to experience mental health problems beyond high stress levels (Parkes, Caravale, Marcelli, Franco, & Colver, 2011; Raina et al, 2005). Compared to mother caregivers of children with other disabilities, it has been reported that caregivers of children with ASD have higher levels of depression and anxiety but lower levels of psychological wellbeing (Benson & Karlof, 2009; Ekas, Whitman, & Shivers, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared to mother caregivers of children with other disabilities, it has been reported that caregivers of children with ASD have higher levels of depression and anxiety but lower levels of psychological wellbeing (Benson & Karlof, 2009; Ekas, Whitman, & Shivers, 2009). Depression is a particularly prevalent psychological issue among mothers of children with ASD (Parkes et al, 2011). It has been reported that mother caretakers with depression exhibit negative parenting behaviours and experience other psychological problems such as anxiety and isolation (Parkes et al, 2011; Raina et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Each motor module involves a basic activation pattern with variable weights of distribution to different muscles [7,8]. In this sense, the concept of muscle synergy has emerged in neuroscience and has been proposed as a mechanism for neural control of normal movement [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the concept of muscle synergy has emerged in neuroscience and has been proposed as a mechanism for neural control of normal movement [9]. Muscle synergies in healthy subjects represent functional muscle coordination patterns used to reliably produce motor functions during natural motor behaviors (4-5 synergies for gait) [7,9,10]. Interestingly, a reduced number of synergies during gait have been reported for children with CP (2-3 synergies).…”
Section: Introductionmentioning
confidence: 99%